(3TQM GdTeSjIs - (3YHO Gddg Ydj Hf eMeO Hf GdMSjfs; (3GdfXGe GdfjSGHhQj , GdMSf Hf eMeO Hf GdMSjf Gdbej GdfjSGHhQj, fXGe GdOjf GdCYQL,J (B850 (3g` s ((3eNOhe jhfS s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdCMO GdefRg Yf GdJKdjK hGdETQGc hGdJeGKd GdChd GdaQO GdebOS Yf GdQhM hGdJQcjH s
(3BNQgG (B:s
(3hbSefG GdeLehY GdChd Ydi GdeLehY GdKGfi hfNJe GdcdGe gGgfG MGeOjf Gddg s
(3GdfSNI HgG MhGTs
(3GfXQ TeSjI GdMSGH ai cTa GdXfhf L(B2 (3U` (B1062s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B216 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B281s
Keywords: (3GdQjGVjGJs